2^- 3x = 6^x + 4
Solution: x = - 4ln(6)/ln(48) Decimal: (- 1.85137.....)
Solve For X: Step by Step:
2^(- 3x) = 6^(x + 4)
Solve Exponent:
2^-3 = 6^x + 4
log (2^-3x) = log (6^x + 4) (Take log of both sides):
( - 3x) * (log (2)) = (x + 4) * (log (6))
- 3x = (log (6)/(log (2) * (x + 4)
- 3x = 2.584963 * (x + 4)
- 3x = 2.584963x + 10.339852
Simplify both sides of the Equation:
- 3x - 2.584963x = 2.584963x + 10.339852 - 2.584963x
Subtract: 2.584963x From both sides:
- 5.584963x = 10.339852
- 5.584963x = 10.339852
- 5.584963 =====> - 5.584963
Divide both sides by: ===> - 5.584963
Hence: x ===> - 1.851373
Answer: x = - 1.851373
Hope that helps!!!!! : )